2015
DOI: 10.1073/pnas.1512561112
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution epitope mapping by HX MS reveals the pathogenic mechanism and a possible therapy for autoimmune TTP syndrome

Abstract: Acquired thrombotic thrombocytopenic purpura (TTP), a thrombotic disorder that is fatal in almost all cases if not treated promptly, is primarily caused by IgG-type autoantibodies that inhibit the ability of the ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) metalloprotease to cleave von Willebrand factor (VWF). Because the mechanism of autoantibody-mediated inhibition of ADAMTS13 activity is not known, the only effective therapy so far is repeated whole-body plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 47 publications
2
60
0
Order By: Relevance
“…Our finemapping study of anti-ADAMTS13 antibodies demonstrated that the RRY motif in the spacer domain of ADAMTS13 is the frequent target of anti-ADAMTS13 IgGs in patients with acquired TTP. 40 HNPs share the same motif that is present in the ADAMTS13-spacer domain; therefore, it is possible that the released HNPs may boost the formation of a specific pathogenic autoantibody that binds the exosite 3 (RRYGEE) in the spacer domain of ADAMTS13. A monoclonal anti-human IgG (scFv4-20) isolated by phage display from a patient with acquired TTP appears to bind HNPs (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our finemapping study of anti-ADAMTS13 antibodies demonstrated that the RRY motif in the spacer domain of ADAMTS13 is the frequent target of anti-ADAMTS13 IgGs in patients with acquired TTP. 40 HNPs share the same motif that is present in the ADAMTS13-spacer domain; therefore, it is possible that the released HNPs may boost the formation of a specific pathogenic autoantibody that binds the exosite 3 (RRYGEE) in the spacer domain of ADAMTS13. A monoclonal anti-human IgG (scFv4-20) isolated by phage display from a patient with acquired TTP appears to bind HNPs (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The autoantibodies bind to the spacer domain of ADAMTS13, which may physically block its substrate recognition. 7 The inability to cleave newly released ultralarge (UL) VWF results in the accumulation of ULVWF polymers on endothelial cells 25 and in the circulation. 26 Consequently, the ULVWF multimers serve as templates for rapidly recruiting platelets, 27,28 neutrophils, 28,29 and complement components 30 from the circulation to the sites of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with plasma infusion, aimed at increasing plasma ADAMTS13 activity to greater than 5%, is clinically effective in hereditary TTP. 6 In patients with acquired TTP, the immunoglobulin (IgG) type of autoantibodies, which bind primarily to the spacer domain of ADAMTS13, 7 result in competitive inhibition of plasma ADAMTS13 activity. Therapeutic plasma exchange, often used in combination with immunosuppression, including corticosteroids, vincristine, cyclophosphamide, and rituximab, etc., remains the treatment of choice for acquired TTP with inhibitors.…”
Section: Human Neutrophil Peptides and Complement Factor Bb In Pathogmentioning
confidence: 99%
“…Co-crystallization provides unambiguous epitope identification but can require considerable effort and generation of many antigen variants to identify one that is compatible with crystallization (2). Mass spectrometry-based methods utilizing hydrogen/ deuterium exchange identify epitopes to a ϳ5-amino acid resolution only under rigorous control experiments that limit throughput (16,17). Competing display-based methods use many sorts (18), identify only partial epitopes (19,20), or are limited by restricting mutations to alanine (21).…”
mentioning
confidence: 99%